2021
DOI: 10.3892/etm.2021.10909
|View full text |Cite
|
Sign up to set email alerts
|

LPS‑induced inflammatory response and apoptosis are mediated by Fra‑1 upregulation and binding to YKL‑40 in A549 cells

Abstract: Acute respiratory distress syndrome (ARDS) is a multifactorial syndrome that leads to increased morbidity and mortality in infants and children. The identification of novel biomarkers is critical for the treatment of ARDS. The present study aimed to investigate the effects of chitinase-3-like-1 protein (CHI3L1 or YKL-40) in an in vitro model of ARDS and to explore the potential underlying mechanisms. The in vitro model of ARDS was established in A549 alveolar epithelial type II cells, which were treated by lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…injection of lipopolysaccharide (LPS) is a widely accepted method for establishing animal models of sepsis. Increasing in vivo studies have shown that LPS-induced inflammation causes inappropriate activation of microglia and astrocytes, damages the BBB, and negatively affects mitochondrial function, oxidative/nitrative stress, and apoptosis [ 20 , 21 ]. Although mangiferin shows excellent protective effects against sepsis-induced lung or kidney injury [ 14 , 15 ], the neuroprotective effects of mangiferin have not been investigated in LPS-induced sepsis using primary cultured hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…injection of lipopolysaccharide (LPS) is a widely accepted method for establishing animal models of sepsis. Increasing in vivo studies have shown that LPS-induced inflammation causes inappropriate activation of microglia and astrocytes, damages the BBB, and negatively affects mitochondrial function, oxidative/nitrative stress, and apoptosis [ 20 , 21 ]. Although mangiferin shows excellent protective effects against sepsis-induced lung or kidney injury [ 14 , 15 ], the neuroprotective effects of mangiferin have not been investigated in LPS-induced sepsis using primary cultured hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Although the systemic inflammation after cecal ligation was not severe enough to induce kidney or liver injury, different from the inflammation of the gut–kidney–liver axis in sepsis [ 7 ], the significant inflammatory responses in cecal-ligated mice were demonstrated by an increase in apoptosis of spleen. Indeed, the overwhelming inflammatory activation can cause apoptosis in several cell types is well-known [ 27 , 61 ].…”
Section: Discussionmentioning
confidence: 99%